PPO.66 The Shirodkar procedure for cervical cerclage: a safe and effective alternative to the McDonald suture. (9th June 2014) - Bonney, EA; Collins, V; Gees, E; Mweemba, M; Simpson, NAB
Abstract : Introduction: Around 11, 000 infants are born < 33 weeks gestation annually in the UK. Cervical weakness is associated with midtrimester birth, and placement of a reinforcing suture is a strategy used to preserve or restore both cervical strength and length. McDonald's approach encircles the vaginal portion of the cervix, the Shirodkar procedure uses colpotomies to place the suture higher up, at the level of the internal os. We examined the efficacy of this approach in our practice. Study Design: Procedural and pregnancy outcome data were collected from women who had a Shirodkar suture inserted between June 2006 and September 2012 at Leeds Teaching Hospitals. Exclusion criteria for this study included incomplete data, insertion of more than one stitch in one pregnancy and multiple pregnancy. Success was defined as the delivery of a baby who survived till discharge from hospital. The median gestational age (MGA) was also calculated, and comparisons made between elective, ultrasound-indicated and rescue procedures. Results: 139 women had a Shirodkar suture inserted. 101 were elective procedures, 30 ultrasound-indicated and 8 were performed in the presence of visible membranes. Elective Shirodkar cerclage produced a success rate of 95.9% and conferred a MGA of 38.0 weeks. Ultrasound-indicated cerclage gave a success rate of 93.3% with a MGA of 37.5 weeks. The success rate for rescue Shirodkar cerclage was 75.0% with a MGA of 33.5 weeks. There were 2 reported complications. Conclusion: Shirodkar cerclage is a safe and effective alternative to the McDonald approach in elective, ultrasound-indicated, and rescue suture settings.